2010
DOI: 10.1007/s00417-010-1469-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sweep VEP parameters on visual acuity and contrast thresholds in children and adults

Abstract: A temporal frequency of 7.5 Hz, a stimulus area of 4° or larger for VA and 10° or larger for contrast thresholds, and the use of a fixation target gave more viable readings, and may be indicated for future application. Consideration of the number of viable readings showed more differences between parameters than the actual thresholds, and it is suggested that more readings presumably would yield more reliable threshold measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…However, since the acuity is extrapolated from the higher spatial frequencies, this decreased signal magnitude for the lower spatial frequencies does not affect the results. Similar observations have been made by Tyler et al [29] and Almoqbel et al [30]. Different stimulus screen sizes will have an additional affect if sVEP comparisons are made in infants or children.…”
Section: Discussionsupporting
confidence: 77%
“…However, since the acuity is extrapolated from the higher spatial frequencies, this decreased signal magnitude for the lower spatial frequencies does not affect the results. Similar observations have been made by Tyler et al [29] and Almoqbel et al [30]. Different stimulus screen sizes will have an additional affect if sVEP comparisons are made in infants or children.…”
Section: Discussionsupporting
confidence: 77%
“…One of the only studies addressing this issue compared visual acuity and contrast thresholds obtained for two electrode placements of five electrodes in the occipital region, with a 2-to 3-cm shift of the electrodes between the two placements. 18 This study showed no significant effect of electrode placement on visual acuity and contrast thresholds. However, even though the authors compared these two placements, they did not compare electrodes individually.…”
mentioning
confidence: 87%
“…These steps were defined as the epochs either above or below the average thresholds found in previous comparable experiments. 4,18,20,25,30,35 More precisely, for visual acuity, this corresponded to the nine steps with spatial frequency from 2.7 to 9.7 cpd for group E, and to the seven steps from 3.8 to 9.4 cpd for group AA. For contrast sensitivity, this corresponded to the nine steps with contrast from 1.5% to 16%.…”
Section: Eeg Analysismentioning
confidence: 99%
“…The VEP has long been used as a clinical tool to determine if the primary afferent visual pathway is intact, as well as to assess an individual’s visual acuity [2,3,4]. Using high-contrast pattern-reversal stimuli, which consist of a black-and-white checkerboard pattern changing phase with constant mean luminance, the pattern VEP produces low variability of waveform both within an individual subject and across subjects [1].…”
Section: Introductionmentioning
confidence: 99%